Participatory research in the alto camaquã: basis for building knowledge of family ranchers (Semiárida, 2020)
Participatory research is a tool that can be used in the construction of collective strategies for endogenous development planning. In this sense, participatory research is being conducted by the staff of the Laboratory for Studies in Agroecology and Natural Resources of the Southern Cattle Research Center (LABECO CPPSul) with family ranchers in the region of the Territory of the Upper Camaquã. Thus, we seek a balance between production and environmental conservation from processes of building research "multi-actor", where all subjects involved (researchers, extension workers and farmers) have the same degree of importance in making livestock durable.
Keywords: Environmental Conservation; Endogenous; Livestock